2022
DOI: 10.1088/1741-4326/ac77e6
|View full text |Cite
|
Sign up to set email alerts
|

Neural net modeling of equilibria in NSTX-U

Abstract: Neural networks (NNs) offer a path towards synthesizing and interpreting data on faster timescales than traditional physics-informed computational models. In this work we develop two neural networks relevant to equilibrium and shape control modeling, which are part of a suite of tools being developed for the National Spherical Torus Experiment-Upgrade (NSTX-U) for fast prediction, optimization, and visualization of plasma scenarios. The networks include Eqnet, a free-boundary equilibrium solver trained on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Throughout the course of developing our NN model and training on various iterations of the processed data, we investigated many variations in the architecture. In general, we found that as long as the activation functions capture the range of the outputs, the number of nodes is sufficiently large, and we trained for a sufficient number of epochs, we obtained accurate inferences of the ψ (R, Z), global parameters, EFIT pressure profile, and EFIT current profile (consistent with the conclusions in [24,43,44]).…”
Section: Hyper-parameter Tuningsupporting
confidence: 71%
See 1 more Smart Citation
“…Throughout the course of developing our NN model and training on various iterations of the processed data, we investigated many variations in the architecture. In general, we found that as long as the activation functions capture the range of the outputs, the number of nodes is sufficiently large, and we trained for a sufficient number of epochs, we obtained accurate inferences of the ψ (R, Z), global parameters, EFIT pressure profile, and EFIT current profile (consistent with the conclusions in [24,43,44]).…”
Section: Hyper-parameter Tuningsupporting
confidence: 71%
“…The choice for this particular MLP design was partially motivated by previous experience that investigated the performance of simple MLP NNs when inferring EFIT solutions. The architecture decisions of such an MLP NN are based on initial studies throughout the development of this work and others (see, for example, [24,43,44]) that produced outputs with sufficient accuracy (i.e. high R 2 values and profiles or contours that visually agreed with the solution) to capture the features of the EFIT solution 7 .…”
Section: The Learning Modelmentioning
confidence: 99%
“…In tokamaks the accurate measurement and control of the magnetic configuration is essential to achieve the required performances [37]. This aspect has become increasingly important in the last years, due to the continuous increase of the scenarios' sophistication and several new methodologies, also based on artificial intelligence, have been developed [38][39][40][41]. From the hybrid scenario to various small or free edge localised modes (ELMs) regimes, fine tuning of the fields is indispensable for both the quality and the stability of the plasmas.…”
Section: Equilibrium Reconstructionmentioning
confidence: 99%
“…We achieve this by utilizing machine learning (ML) techniques based on a numerically generated equilibrium database. Machine learning has been widely used in fusion research, for example in plasma instability and disruption predictions [3][4][5][6][7][8][9][10][11][12][13][14], magnetic control [15], non-powerlaw scaling [16], turbulent transport [17][18][19] and plasma profile predictions [20,21], as well as fast magnetic equilibrium reconstruction [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%